Importance of sewage sludge stabilization for agricultural valorization in soil conditioning - Meneses Solis, Teofilo Eustedio (2022)
The influence of the addition of alkaline mass in the stabilization process of two waste water sludges was studied. The increase in the PH of the sludge, carrying it to values near to twelve, is due to the increase of alkaline mass additions during the stabilization of the residual sludge. This technique was used to stabilize the sludge and to give an agricultural valorization to the residual sludge. In this context, the problematic characteristics present in the sludge will lead us to a preliminary treatment of the sewage sludge.